2020
DOI: 10.5114/cipp.2020.94317
|View full text |Cite
|
Sign up to set email alerts
|

Autistic traits, adolescence, and anti-social peer pressure

Abstract: The potential role of autism as a moderator of conformity has recently been investigated by a small number of studies. However, as yet, no consensus has emerged as to whether autism or autistic traits can moderate the degree to which people attend to and are influenced by social pressure, nor whether there are specific circumstances under which this might occur. The current study adds to this ambiguous literature by looking at whether autism and autistic traits are associated with conformity in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Furthermore, this finding partly contradicts the results from Nenniger et al (2021), who found that girls' autistic traits are influenced by their peers. On the other hand, this finding corresponds with many studies showing that individuals with high levels of autistic traits are less sensitive to social or peer influence (Izuma et al, 2011;Yafai et al, 2014;van Hoorn et al, 2017;Verrier et al, 2020). Second, I hypothesized that higher classroom levels of social skills at the beginning of the school year would be related to an increase in individual social skills at the end of the school year.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Furthermore, this finding partly contradicts the results from Nenniger et al (2021), who found that girls' autistic traits are influenced by their peers. On the other hand, this finding corresponds with many studies showing that individuals with high levels of autistic traits are less sensitive to social or peer influence (Izuma et al, 2011;Yafai et al, 2014;van Hoorn et al, 2017;Verrier et al, 2020). Second, I hypothesized that higher classroom levels of social skills at the beginning of the school year would be related to an increase in individual social skills at the end of the school year.…”
Section: Discussionsupporting
confidence: 76%
“…This finding is at odds with studies on typical development, which show that for many behavioral domains, future individual behavior can be predicted by earlier mean classroom behavior when controlling for earlier individual behavior in regular classrooms (e.g., Müller and Zurbriggen, 2016). However, this result is again in line with studies showing that individuals with high levels of autistic traits are less influenced by others (Izuma et al, 2011;Yafai et al, 2014;van Hoorn et al, 2017;Verrier et al, 2020).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Second, we investigated whether boys and girls with ID and high levels of autistic traits differ in their susceptibility to peer influence. Since boys and girls with high levels of autistic traits differ, for example, in terms of social skills, social relationships, or social motivation, gender seems like an especially relevant variable in the context of peer influence (see also, Verrier et al, 2020 ). Given the described differences in social competence between girls and boys with high levels of autistic traits, we expected that target girls are more susceptible to peer influence on autistic traits than target boys (Hypothesis 2).…”
Section: Introductionmentioning
confidence: 99%